Analisis Pengaruh Perencanaan Kerja, Koordinasi Kerja dan Kepemimpinan Partisipatif Terhadap Kinerja Pegawai Pada Kantor Kecamatan Alor Selatan Kabupaten Alor - Domialos Yeremias Onlan (Jurnal Ilmiah Wahana Pendidikan, 2023)
Performance is the result of work achieved by an employee or employees in carrying out their duties in accordance with the responsibilities given to them. Factors that influence performance in this study include work planning, work coordination, and participatory leadership. This study aims to determine the effect of Work Planning, Work Coordination and Participatory Leadership on employee performance. This type of research is quantitative research with data collection techniques, namely observation, interviews, and documentation studies. This study used population primary data and samples were employees at the South Alor District Office, Alor Regency, totaling 21 people. And the sampling technique in this study is a saturated sample. The statistical method used in this study is multiple linear regression. The results of this study indicate that: (1). partially the Work Planning variable has a significance value of 0.001 or 0.1% where this value is smaller than the alpha value of 0.05 or 5% so that the results of this study accept H1 which states that the Work Planning variable has a partial positive effect on employee performance in Alor Selatan District Office, Alor Regency. (2). partially the Work Coordination variable has a significant value of 0.007 or 2.3% where this value is smaller than the alpha value of 0.05 or 5% so that the results of this study accept H2 which states that the Work Coordination variable has a partial positive effect on employee performance at South Alor District Office Alor Regency (3). partially the Participatory Leadership variable has a significant value of 0.033 or 0.5% where this value is smaller than the alpha value of 0.01 or 5% so that the results of this study accept H3 which states that the Participatory Leadership variable partially has a positive effect on employee performance at Alor Selatan District Office, Alor Regency. (4). simultaneously the variables Work Planning, Work Coordination and Participatory Leadership have a significant value of 0.000 or 0.00% where this value is smaller than the alpha value which is equal to 0.05 which is 5% so that the results of this study simultaneously receive H4 which states that the Work Planning variable , Work Coordination and Participatory Leadership have a positive effect on employee performance at the Alor Selatan District Office, Alor Regency. (5). The magnitude of the influence of the variables Work Planning, Work Coordination and Participatory Leadership on Employee Performance at the Alor Selatan District Office, Alor Regency, is 73.9%, this study simultaneously received H5